A study on the challenges and opportunities of building a still wine brand in Madeira Island - Gomes, João Guilherme Correia (2022)
Wine represents one of the pillars of Madeira’s economy. Madeira Wine has delighted tourists and embellished dinner tables all over the world for many centuries. However, the strong presence of Madeira’s fortified wine on consumer’s minds tends to overshadow the potential of its discreet young brother: the still wine. The still wine scene in Madeira officially began in 1992, when Madeira Wine Company released Atlantis, the first still wine produced and bottled in Madeira. Since then, many were the producers that jumped on board of this challenging adventure, despite the evident barriers around this endeavor. Madeira’s still wine panorama is growing stronger every year but it is yet to penetrate successfully the national and international market. This work investigates the challenges that arise from building a still wine brand in Madeira and the opportunities there are to explore in the wine market, with a special focus on whether Madeirans consume and are aware of the potential of their own wine. This thesis follows the case of Ilha, a recently founded Madeiran still brand by a long-time expert in the field, that successfully imposed its name in the wine world in a short period of time. The case of Ilha encompasses the ideal variables for exploring the themes previously mentioned.